Expanding the Curriculum in a School of Public Health - Jordan, Evan J.; Young, Sarah J.; Menachemi, Nir (Frontiers in Public Health, 2021)
Public health education has long been concentrated in a core set of public health disciplines such as epidemiology, biostatistics, and environmental health. Despite leaps forward in our understanding of the myriad influences on public health, little has changed in the organization of our educational systems. One issue brought to the forefront of public consciousness by the COVID-19 pandemic is the importance of leisure experiences like going for a walk in the park to mental and physical wellbeing. In this descriptive best practice article, we discuss our approach to expanding the notion of a school of public health and provide examples of how disciplines and subjects outside of the ‘norms’ of public health education, like leisure studies, can help better prepare students for their future in the field. Leisure studies is just one subject area of many that can add value to public health pedagogy, and we envision many other subject areas and departments integrating into schools of public health in the future.